Financial policies in emerging markets - Bléjer, Mario I.; Skreb, Marko, 1957- (MIT Press, 2002)
An overview of the financial vulnerability of emerging market economies and how the impact of exchange rate regimes affects this vulnerability. The 1994-1995 Mexican crisis was the first in a succession of financial crises to hit emerging markets in Thailand, Indonesia, Malaysia, South Korea, Russia, Brazil, Argentina, and Turkey. In almost all these cases, problems in the banking sector played a key role. Any analysis of recent developments in emerging market economies must consider two questions: What is the degree of financial vulnerability in emerging market economies, and what, if any, is the connection between the exchange rate regime and financial vulnerability?This book furthers understanding of the impact of financial policies on emerging market economies. Following an introduction by the editors, the book contains two main sections. The first presents theoretical and empirical evidence on the relation between financial policy and financial vulnerability. The second considers financial policy in central and eastern Europe in terms of the euro and the European Monetary Union. Although there is no clear-cut answer to which exchange rate regime works best, the book concludes that the financial vulnerability of emerging market economies suggests the advisability of greater caution in financial system liberalization and management.